Amphetamine and Methamphetamine Differentially Affect Dopamine Transporters in Vitro and in Vivo - Goodwin, J. Shawn (American Society for Biochemistry and Molecular Biology, 2009)
The psychostimulants d-amphetamine (AMPH) and methamphetamine (METH) release excess dopamine (DA) into the synaptic clefts of dopaminergic neurons. Abnormal DA release is thought to occur by reverse transport through the DA transporter (DAT), and it is believed to underlie the severe behavioral effects of these drugs. Here we compare structurally similar AMPH and METH on DAT function in a heterologous expression system and in an animal model. In the in vitro expression system, DAT-mediated whole-cell currents were greater for METH stimulation than for AMPH. At the same voltage and concentration, METH released five times more DA than AMPH and did so at physiological membrane potentials. At maximally effective concentrations, METH released twice as much [Ca(2+)](i) from internal stores compared with AMPH. [Ca(2+)](i) responses to both drugs were independent of membrane voltage but inhibited by DAT antagonists. Intact phosphorylation sites in the N-terminal domain of DAT were required for the AMPH- and METH-induced increase in [Ca(2+)](i) and for the enhanced effects of METH on [Ca(2+)](i) elevation. Calmodulin-dependent protein kinase II and protein kinase C inhibitors alone or in combination also blocked AMPH- or METH-induced Ca(2+) responses. Finally, in the rat nucleus accumbens, in vivo voltammetry showed that systemic application of METH inhibited DAT-mediated DA clearance more efficiently than AMPH, resulting in excess external DA. Together these data demonstrate that METH has a stronger effect on DAT-mediated cell physiology than AMPH, which may contribute to the euphoric and addictive properties of METH compared with AMPH.